2017
DOI: 10.1016/j.jaci.2016.07.012
|View full text |Cite
|
Sign up to set email alerts
|

IL-4 impairs wound healing potential in the skin by repressing fibronectin expression

Abstract: Background Atopic dermatitis (AD) is characterized by intense pruritis and is a common childhood inflammatory disease. Many factors are known to affect AD development, including the pleiotropic cytokine interleukin (IL)-4. Yet, still little is known regarding the direct effects of IL-4 on keratinocyte function. Objective and Methods: In this report, RNA-seq and functional assays were used to define the impact of the allergic environment on primary keratinocyte function and wound repair in mice. Results Acute… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
35
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 59 publications
(42 citation statements)
references
References 50 publications
3
35
0
1
Order By: Relevance
“…Consistent with this notion, it has been recently demonstrated that excisional wound closure is significantly delayed in mice overexpressing IL-4 or the active form of STAT6, a transcription factor critical for the IL-4/IL-13 signals that manifest ADlike skin disorders. 40,41 These results support the intriguing possibility that periostin mis-expression may be involved in the impaired wound repair seen in AD patients.…”
Section: Discussionsupporting
confidence: 63%
“…Consistent with this notion, it has been recently demonstrated that excisional wound closure is significantly delayed in mice overexpressing IL-4 or the active form of STAT6, a transcription factor critical for the IL-4/IL-13 signals that manifest ADlike skin disorders. 40,41 These results support the intriguing possibility that periostin mis-expression may be involved in the impaired wound repair seen in AD patients.…”
Section: Discussionsupporting
confidence: 63%
“…In the airways, IL-13 has been shown to induce mucus production via the IL-4-receptor α, Stat6 and Spdef pathway [47,48]. This pathway has been implicated in healing, but with contrasting results: IL-4 has been demonstrated to impair wound healing in the skin [50], whereas Stat6 −/mice display delayed wound healing in mice treated with 2,4,6-trinitrobenzenesulfonic acid [51] We have previously shown that mucin production and vesicle transport rate decrease during acute and chronic infection with Helicobacter pylori in the murine stomach [52]. Similar to C. rodentium, H. pylori is associated with a Th1/17 cytokine response, but in contrast, H. pylori causes a chronic infection associated with reduced expression of IL-4 [53].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, Treg depletion caused severe autoimmune gastritis that was ameliorated by loss of IL‐4 . Interestingly, negative effects of increased levels of IL‐4 on wound healing have been described , suggesting that upregulation of this cytokine further contributes to the impaired healing in Treg‐depleted mice. However, preliminary experiments showed that antibody‐mediated IL‐4 neutralization does not rescue the wound healing defect in Treg‐depleted mice, but rather has the opposite effect.…”
Section: Discussionmentioning
confidence: 99%